Accelerated HF-rTMS in treatment-resistant unipolar depression: Insights from subgenual anterior cingulate functional connectivity. (May 2014) - Baeken, Chris; Marinazzo, Daniele; Wu, Guo-Rong; Van Schuerbeek, Peter; De Mey, Johan; Marchetti, Igor; Vanderhasselt, Marie-Anne; Remue, Jonathan; Luypaert, Robert; De Raedt, Rudi
Abstract: Objectives. Intensified repetitive transcranial magnetic stimulation (rTMS) applied to the left dorsolateral prefrontal cortex (DLPFC) may result in fast clinical responses in treatment resistant depression (TRD). In these kinds of patients, subgenual anterior cingulate cortex (sgACC) functional connectivity (FC) seems to be consistently disturbed. So far, no de novo data on the relationship between sgACC FC changes and clinical efficacy of accelerated rTMS were available. Methods. Twenty unipolar TRD patients, all at least stage III treatment resistant, were recruited in a randomized sham-controlled crossover high-frequency (HF)-rTMS treatment study. Resting-state (rs) functional MRI scans were collected at baseline and at the end of treatment. Results. HF-rTMS responders showed significantly stronger resting-state functional connectivity (rsFC) anti-correlation between the sgACC and parts of the left superior medial prefrontal cortex. After successful treatment an inverted relative strength of the anti-correlations was observed in the perigenual prefrontal cortex (pgPFC). No effects on sgACC rsFC were observed in non-responders. Conclusions. Strong rsFC anti-correlation between the sgACC and parts of the left prefrontal cortex could be indicative of a beneficial outcome. Accelerated HF-rTMS treatment designs have the potential to acutely adjust deregulated sgACC neuronal networks in TRD patients.